Facts About Fluoride - Anne Kendall; Linda B. Bobroff (EDIS, 2017)
Fluoride is important for healthy bones and teeth. It increases the density of bones and also can stimulate the growth of new bone. Fluoride increases the amount of minerals in our teeth and even can reverse the progression of dental cavities (also called caries). This 2-page fact sheet is a minor revision written by Anne Kendall and Linda B. Bobroff, and published by the Department of Family, Youth and Community Sciences, November 2017.